Personal development in a high-performance sport environment - Jørgensen, H.; Mosewich, A.; McHugh, T. L.; Holt, N. L. (Journal of Exercise, Movement, and Sport, 2021)
Personal development is important to help athletes successfully deal with challenges and transitions throughout their career (Devaney et al., 2018). The purpose of this study was to develop a grounded theory of how to promote personal development in a high-performance sport environment. Interviews were conducted with 32 individuals who were involved in the Canadian national biathlon teams. The sample was comprised of 18 athletes (9 women, 9 men, Mage = 20.8 years, SD = 2.9), 5 coaches (1 woman, 4 men), 3 technical leaders (2 women, 1 man), and 6 parents (3 mothers, 3 fathers). Following Straussian grounded theory methodology (Corbin & Strauss, 2015), there was an iterative process of data collection and analysis. Analytic techniques included open coding, constant comparison, questioning, memoing, diagramming, and theoretical integration of concepts and categories. The grounded theory of personal development was built around the core category of "continuous and individual development." The core category was underpinned by three categories: (a) psychological skills and characteristics, which referred to skills (e.g., realistic self-evaluation, goal-setting) and characteristics (e.g., hard-work ethic, independence) that promoted athletes' personal development; (b) social support systems, which involved emotional, esteem, informational, and tangible support; and (c) transitions and life lessons, which encompassed events that influenced the athletes' personal development. The theory predicts that athletes can experience personal development when they develop psychological skills and characteristics, use their social support systems, and learn from transitions and life lessons. The theory will be used to design a personal development program for high-performance athletes.